PRODUCTION FUNCTIONS OF THE RUSSIAN ECONOMY SECTORS TAKING INTO ACCOUNT EFFECT OF ECONOMY AT A SCALE - M. Kuternin (Publishing House of the State University of Management, 2018)
The article deals with to the creation of macroeconomic production functions of the Russian economy for the sector of natural monopolies and the competitive sector of the economy. It is shown that creation of the effective system of the Russian Federation economy state regulation founded on the use of natural monopolies as the main instrument of competitive economy management requires the use of effect economy at a scale that has to be reflected in the production function of the natural monopolies sector. The technique of reflection of effect economy at a scale in production function is developed, and the production functions of two sectors of the Russian economy taking into account this effect has been built by econometric methods. These production functions are offered to be used at development of the system of indirect state regulation of economy of the Russian Federation.